An Ex Ante Evaluation Framework for the Regional Impact of Publicly Supported R&D Projects - Stephen Roper; Nola Hewitt-Dundas; James H Love (European Regional Science Association (ERSA), 2003)
This paper draws on the knowledge-base implicit in ex post evaluations of publicly funded R&D and other related conceptual and empirical studies to suggest a framework for the ex ante evaluation of the regional benefits from R&D projects. The framework developed comprises two main elements: an inventory of the global private and social benefits which might result from any R&D project; and, an assessment of the share of these global benefits which might accrue to a host region, taking into account the characteristics of the R&D project and the region's innovation system. The inventory of global benefits separately identifies private and social benefits and distinguishes between increments to public and private knowledge stocks, benefits to R&D productivity and benefits from commercialisation. Potential market and ?pure? knowledge spillovers are also considered separately. The paper concludes with the application of the framework to two illustrative case-studies one relating to a collaborative company-university project and one relating to a university only research centre.
Keywords: 330